PTEN Immunohistochemistry: A New Approach for Diagnosis of Intestinal Neuronal Dysplasia Type B - Terra, Simone Antunes [UNESP]; de Arruda Lourenção, Pedro Luiz Toledo [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP] (Archives of Pathology and Laboratory Medicine, 2023)
Context.—Intestinal neuronal dysplasia type B (IND B) is a complex entity involving the enteric nervous system, clinically manifested with constipation in infancy. Diagnosis has been established by histopathologic analysis of rectal biopsies. However, the criteria for the diagnosis have been questioned and modified, hindering diagnostic practice. Objective.—To analyze the applicability of PTEN immunohistochemistry in the diagnosis of IND B and to compare with control cases and cases of Hirschsprung disease (HD). Design.—PTEN immunohistochemical expression was analyzed in colorectal samples from 29 cases of IND B and compared with 4 control cases and 6 cases of HD. The pattern of PTEN immunoexpression was analyzed in glial cells of the submucosal and myenteric nerve plexuses and in neural fibrils of the muscularis propria using a scoring system. Results.—Marked reduction or absence of PTEN expression was observed in glial cells of the submucosal nerve plexuses in all cases of the IND B group and in the myenteric nerve plexuses in 28 of 29 cases (96.5%). Lack of PTEN expression was detected in neural fibrils within the muscularis propria in 21 of 29 cases (72%) of the IND B group. PTEN expression was positive in the same neural structures of the control and HD groups. Conclusions.—PTEN immunohistochemistry may be a valuable tool in the diagnostic evaluation of IND B. Lack of or reduction of PTEN expression in neural fibrils within the muscularis propria suggests that involvement of the neuromuscular junction may be a key event in the pathogenesis of the motility disturbance occurring in IND B.